A performance da memória e as trabalhadoras domésticas: um estudo entre Antropologia e Ciência da Informação na exposição de longa duração do museu Muquifu - Samanta Coan (2022)
This thesis is the result of a research carried out at the Museu dos Quilombos e Favelas Urbanos (Muquifu), inaugurated by a group of residents of Aglomerado Santa Lúcia (also known as Morro do Papagaio) on November 20, 2012. It is categorized as a community and territory museum, which works with collections donated or lent by the community. In the context of Muquifu, the investigative focus was on three long-term exhibitions: Doméstica, da escravidão à extinção – uma antologia do quartinho de empregada no Brasil (Domestic, from slavery to extinction – an anthology of the domestic worker's room in Brazil) [2013]; Uniformes de domésticas: da escravidão aos dias atuais (Domestic worker uniforms: from slavery to the present day) [2015]; e Presente de Patroa (Gift from the employer) [2018]. For the analysis, the performance of the domestic worker's memory is approached and the intersectionality of gender, race, and class are discussed as a determining factor (historically and in the present) of the life condition and experience of subordination of working black women and favela residents in Belo Horizonte city. Thus, this thesis proposes to contribute with a “thick description” of these exhibitions, aiming to highlight the importance of the project of community and territorial museums, such as Muquifu, which are committed to safeguarding and disseminating the representations of memories (objects valued as museum collection and heritage), collaborating with the production of informational and recording sources – of the oral history and life of marginalized people who inhabit the favelas or peripheries –, valuable for reading against the grain of official history. To this end, the thesis is based on the theoretical contribution of performance studies and postcolonial and decolonial records – with emphasis on feminist productions –, among other complementary readings. To discuss the notion of memory triggered in the Muquifu exhibition context, our reference was Diana Taylor's (2013) reflections on archive and repertoire, the vocality in the writings by Paul Zumthor (1993, 2018), whose centrality is the body in performance, and Della Pollock's with oral history (2005; 2008). As for the methodological resources, the work consisted of researching on bibliographic and documental sources (survey and consultation of theoretical and specialized productions on the theme of the thesis); field research guided by the ethnographic method of participant observation and observant participation with the Muquifu Collective, conducting semistructured interviews with women who donated and/or wrote a short story about paid domestic work at the exhibition, as well as informal conversations with Muquifu staff and visitors to the exhibitions. This investigative work started from the following questions: while accessing the exhibitions of the nucleus of paid domestic work, what these people were performing? What do they have to say about themselves and about the paid domestic worker through the museum objects? How does this Museum provide the opportunity for agency and the different identities of the participants through the archives and repertoires? How do the workers affect the producers of this Museum in their expographic conceptions over time? It is concluded that this "community museum in process" seeks to making the visiting public assimilates its political discourse on the subject.